2017
DOI: 10.1111/his.13206
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and immunophenotypical features of hairy cell leukaemia involving lymph nodes and extranodal tissues

Abstract: Although uncommon, HCL should be considered in the differential diagnosis of small B cell neoplasms involving nodal/extranodal sites, given the therapeutic implications. In particular, recent discoveries including detection of the BRAF mutation in nearly all cases of HCL and the availability of an antibody to CD103 for use in paraffin-embedded tissues will facilitate the distinction of HCL from other small B cell lymphomas in the nodal/extranodal setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…Cortazar et al reported that the immunophenotype of nodal/extranodal diseases overlapped with that of other small B-cell lymphomas; proteins expressed by both sets of diseases included CD5 and cyclin D1( 3 ). MCL is a mature B-cell neoplasm that accounts for 3-10% of malignant lymphomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortazar et al reported that the immunophenotype of nodal/extranodal diseases overlapped with that of other small B-cell lymphomas; proteins expressed by both sets of diseases included CD5 and cyclin D1( 3 ). MCL is a mature B-cell neoplasm that accounts for 3-10% of malignant lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…The HCL immunophenotypic profile is characterized by the expression of CD19, CD20, CD22, and CD200. Cyclin D1 is expressed in approximately 50-70% of cases, whereas CD5 is weakly expressed in only approximately 0-2% ( 1 , 3 ). The BRAF V600E gene mutation is found in >97% of HCL cases ( 4 ), and is associated with poor prognosis ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unusual markers in classic HCL like CD38 have been associated with shorter time to progression and next treatment [ 75 ]. Other aberrant markers like CD5 or CD10 have not shown prognostic implications [ [76] , [77] , [78] , [79] ].…”
Section: How To Tell Hcl From Variantsmentioning
confidence: 99%
“…The detection of Annexin A1, TRAP, BRAF and CD72/DBA.44 by IHC may contribute to the diagnosis. The expression of CD5 is exceedingly rare but was described in up to 2% of cases [ 125 , 126 , 127 ]. Together with the positivity for Cyclin D1 in half of the patients and the possible presence of lymphadenopathy, CD5-positive cases can be misdiagnosed as MCL.…”
Section: Lymphomas Rarely Expressing Cd5mentioning
confidence: 99%